Taqwi̅m Tadri̅ba̅t Kita̅b Ta’li̅m al-Lughah al-‘Arabiyyah li as-Ṣhaf ar-Ra̅bi’ min al-Marḥalah al-Ibtida̅iyyah ‘ala Ḍau̅I Ma’a̅yi̅r ‘Abdu ar-Raḥman Ibnu Ibra̅hi̅m al-Fau̅za̅n - Basid, Abdul; Sutaman, Sutaman; Arifa, Zakiya (STAI Ali bin Abi Thalib Surabaya, 2024)
This study aims to find out how to teach Arabic grammar to non-Arabic speakers according to the basis of presenting the material and its relationship to reading skill. The research methodology used by the researchers is the qualitative approach, and the type of research is library research. The sources of data for this research are the book Education by Mahmoud Yunus and books, articles or University journals related to research and analysis. The researchers used the method of analyzing the content of the texts, and the background that drives the researchers to complete this research is what the researchers found that the students saw Arabic grammar as one of the most difficult Arabic subjects and the fact that teachers are not good at managing education, as they do not teach Arabic grammar on the basis of recitation. Good education, and the basis for delivering the subject: 1) From the tangible to the intelligible, 2) From the known to the unknown, 3) From examples to rules or definitions, 4) From simple to complex progression. The application of this basis in teaching Arabic grammar is: 1) Defining the noun and knowledge by mentioning the sign, not defining them terminologically, using visual teaching aids when teaching the hidden pronoun, 2) Restricting the study of annulants to the nominal sentence in teaching grammar and restricting the teaching of the direct and the direct to the verbal and nominal sentences, 3) Using the inductive method and modified texts in teaching grammar, morphology, and rhetoric, 4) mentioning the singular before the compound, and using the functional theory and teaching grammar before rhetoric, that reading skill is due to recognition and understanding, which are related to the student’s proficiency in Arabic grammar.